PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE FLASH PADA PEMBELAJARAN IPA MATERI TATA SURYA KELAS VI SDN KEBON BARU KOTA TANGERANG - Purwati, Purwati; Syachruroji, A.; Nulhakim, Lukman; Andriana, Encep (LPPM Universitas Bina Bangsa, 2024)
This study aims to increase student interest in class VI by using interactive media based on Adobe Flash at SDN Kota Baru. The research method used by the author is the research and development method or Research and Development (R&D) which is the method used to produce certain products and test the effectiveness of these products. With seven stages: problem analysis, data collection, product design, product design validation, product revision, product testing, and final results. To prove the media from Adobe Flash interactive media, validation tests were carried out by media experts and material experts. After testing the product, the subject of this research is class VI SDN Kota Baru students. Based on the validation, it was stated that Adobe Flash interactive learning media was